Renovating the vietnamese communist party : - Stern, Lewis M. (Institute of Southeast Asian Studies, 1993)
The Vietnamese Communist Party has been preoccupied with renewal and reorganization for over a decade. Efforts to eliminate inefficient, ineffective and corrupt cadre; recruit younger, skilled and better educated members; improve basic party chapter-level leadership and organization; and select and train a generation of party secretaries at all levels have limped along since the late 1970s. This book traces the evolution of the reforms of the party organization under Nguyen Van Linh. Under his leadership party reform gained a new lease on life. However, by 1988 Linh was increasingly stymied by the closing of ranks of party conservatives, the glacial speed with which the party organization responded to reform initiatives, and the extent to which ineffective leadership, poor organizing habits and venality had saturated the core of the party